Hubungan Antara Harga Diri Dengan Perilaku Asertif Pada Remaja Di SMA Yayasan Pendidikan Citra Harapan Percut Sei Tuan - Robekka Margretta; Hasanuddin Hasanuddin; Babby Hasmayni (Jouska: Jurnal Ilmiah Psikologi, 2022)
The purpose of this study was to determine the relationship between self-esteem and assertive behavior in SMA Citra Harapan Percut Sei Tuan students. The research hypothesis is that there is a relationship between self-esteem and assertive behavior of SMA Citra Harapan Percut Sei Tuan students. The research sample amounted to 60 students of SMA Citra Harapan Percut Sei Tuan, taken using the Correlation- Product Moment analysis method. There is a positive relationship between self-esteem and assertive behavior in SMA students at the Citra Harapan Education Foundation Percut SeiTuan, the higher the self- esteem, the higher the assertive behavior, and vice versa, the lower the self-esteem, the lower the assertive behavior, where, r is 0, 637 with a significance level of 0.000 0.05. That is, the proposed hypothesis is accepted. The determinant coefficient (r^2) of the relationship between the X variable and the Y variable is r^2 = 0.406. This shows that self-esteem contributes to assertive behavior by 40.6%. Based on the comparison between the Hypothetical Mean and the Empirical Mean, namely, that the Empirical Mean of self-esteem (me = 100.27) is above the Hypothetical Mean (me = 80) it can be concluded that based on the Empirical Mean, the subjects of this study have high self-esteem.